2006
DOI: 10.1534/genetics.105.049650
|View full text |Cite
|
Sign up to set email alerts
|

The twisted Gene Encodes Drosophila Protein O-Mannosyltransferase 2 and Genetically Interacts With the rotated abdomen Gene Encoding Drosophila Protein O-Mannosyltransferase 1

Abstract: The family of mammalian O-mannosyltransferases includes two enzymes, POMT1 and POMT2, which are thought to be essential for muscle and neural development. Similar to mammalian organisms, Drosophila has two O-mannosyltransferase genes, rotated abdomen (rt) and DmPOMT2, encoding proteins with high homology to their mammalian counterparts. The previously reported mutant phenotype of the rt gene includes a clockwise rotation of the abdomen and defects in embryonic muscle development. No mutants have been described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 39 publications
0
43
0
1
Order By: Relevance
“…The addition of a novel, less prevalent, branched form of the glucuronylated core 1 glycan (Structure 5) increases this portfolio to 98% of the total profile. We also detected a group of expected, minor structures (O-Man, O-Glc, monoxylosylated O-Glc, O-GlcNAc) that have been predicted to exist in embryonic tissues based on phenotypes associated with mutations in the proposed biosynthetic enzymes or on the in vitro identification of appropriate enzymatic activities: protein O-mannosyltransferases, rotated/POMT1 and twisted/POMT2; protein O-glucosyltranferase, rumi/Poglut; and O-GlcNAc transferase (OGT) (8,58,59,(67)(68)(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of a novel, less prevalent, branched form of the glucuronylated core 1 glycan (Structure 5) increases this portfolio to 98% of the total profile. We also detected a group of expected, minor structures (O-Man, O-Glc, monoxylosylated O-Glc, O-GlcNAc) that have been predicted to exist in embryonic tissues based on phenotypes associated with mutations in the proposed biosynthetic enzymes or on the in vitro identification of appropriate enzymatic activities: protein O-mannosyltransferases, rotated/POMT1 and twisted/POMT2; protein O-glucosyltranferase, rumi/Poglut; and O-GlcNAc transferase (OGT) (8,58,59,(67)(68)(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%
“…rt 2 and rt p are semilethal P-element insertion alleles as described by Martin-Blanco and Garcia-Bellido (1996). tw 1 is viable and carries an amino acid substitution in the conserved POM domain (Lyalin et al, 2006). Lethal and semilethal alleles were balanced over green fluorescent (GFP)-marked balancers; absence of GFP was used to select homozygous mutant larvae.…”
Section: Drosophila Stocks and Crossesmentioning
confidence: 99%
“…Dg isoforms that lack the mucin-like domain are required to maintain polarity in the follicular epithelium (Schneider et al, 2006), suggesting that the Dg isoforms can have different functional roles in Drosophila. POMTs are also found in Drosophila (Martin-Blanco and Garcia-Bellido, 1996;Ichimiya et al, 2004;Lyalin et al, 2006) and biochemical analysis of Drosophila POMT1, encoded by the gene rotated abdomen (rt; Martin-Blanco and Garcia-Bellido, 1996) and POMT2, encoded by twisted (tw; Lyalin et al, 2006) has demonstrate that these enzymes possess POMT activity similar to their vertebrate homologues (Ichimiya et al, 2004). When transfected together in insect cells they are able to transfer mannose to a GST-␣-Dg substrate generating Olinked mannose (Ichimiya et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O-Mannosylation is essential for maintaining cell shape and cell integrity (21) and contributes to quality control of proteins in the endoplasmic reticulum (ER) in yeast (22,23). Reduction of protein O-mannosyltransferases in Drosophila melanogaster resulted in defects in embryonic muscle development (24)(25)(26)(27) and pomt1 deletion in mouse resulted in embryonic death (28). Recently, we also demonstrated that O-mannosyltranserase was required for muscle development in zebrafish (29).…”
Section: B O-mannosyltransferase (Pomt)mentioning
confidence: 99%